A method for preparing a spectral conversion film
Patent Information
- Application Number
- CN202310521815.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-10
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-05-10
AI Technical Summary
Existing technologies struggle to achieve efficient spectral conversion without altering the structure of solar cells, and existing methods cannot guarantee the transmittance and high-temperature resistance of thin films, resulting in low photoelectric conversion efficiency of solar cells.
A chemical method for preparing rare earth-doped fluoride thin films is adopted. Rare earth RE-doped NaYF4 large-grain thin films are formed by spin coating and hydrothermal growth on glass or quartz substrates. By combining the use of PVP and NaBF4, high transmittance and strong adhesion are achieved.
A high-transmittance spectral conversion film was achieved, which can effectively convert ultraviolet and infrared photons into visible photons, improve the photoelectric conversion efficiency of solar cells, and has high temperature resistance and mechanical peel resistance.
Smart Images

Figure CN116544305B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a spectral conversion thin film, belonging to the field of light conversion material technology. Background Technology
[0002] In the context of energy issues, research on solar cell materials is becoming increasingly urgent. However, the bandgap (E) of the solar cell absorber layer (semiconductor material) is a significant factor. g Due to limitations imposed by spectral density, various solar energy absorbing materials, including crystalline silicon, amorphous silicon, and gallium arsenide, can only achieve high-efficiency photoelectric conversion for photons within their specific spectral ranges. For example, monocrystalline silicon (E g The optimal spectral response range of a 1.1 eV solar cell is approximately between 400 nm and 1100 nm, which is a relatively large range among all solar cells. However, the cell's response speed drops rapidly to short-wavelength and long-wavelength photons outside this range. Experiments and theoretical studies have shown that the transmission loss of typical crystalline silicon solar cells is above 19%, while the losses of novel perovskite, organic, or gallium arsenide cells are between 30% and 50%.
[0003] Researchers are searching for ways to expand the spectral response range of solar cells to increase their photoelectric conversion efficiency. However, changing the cell structure and searching for new solar cell materials would waste human, material, and time resources. Therefore, a shift in research focus is needed to find a spectral conversion material that can convert short-wavelength (high-energy ultraviolet) photons that the cell material cannot fully absorb into mid-to-long-wavelength (visible-near-infrared) photons with higher absorption rates, or convert long-wavelength photons (greater than 1200nm) that the cell cannot absorb into mid-to-long-wavelength photons, without changing the cell structure and light-absorbing materials. This would achieve narrow-band light emission of the solar spectrum, which could significantly improve the efficiency of solar cells without changing the cell structure.
[0004] Fluorides, due to their low phonon energy and stable chemical properties, are commonly used as matrices for high-efficiency spectral conversion materials. Doping a fluoride matrix with rare-earth elements possessing spectral conversion capabilities can achieve either long-wavelength photon upconversion (converting short-wavelength photons) or short-wavelength photon downconversion (converting long-wavelength photons). Rare-earth-doped fluoride powders are simple and convenient to prepare and have been widely used as high-efficiency phosphors. However, when used as the light-absorbing layer in solar cells, the transmittance is significantly reduced due to the powder's opacity and multi-grain boundary scattering. Therefore, there is an urgent need for a method to prepare high-transmittance rare-earth-doped fluoride spectral conversion films that can be directly deposited on encapsulation glass to solve the problems of spectral conversion and high transmittance.
[0005] Chinese Patent 201910148248.5 discloses the following method for preparing a wavelength conversion luminescent film: (1) a mixture of oleic acid and ethanol is used to dissolve rare earth chloride salt and sodium fluoride, and then wavelength conversion luminescent nanoparticles are synthesized by solvothermal method; (2) polymethyl methacrylate (PMMA) particles are dissolved in anisole organic solution to prepare PMMA solution; (3) wavelength conversion luminescent nanoparticles are dispersed in PMMA solution, and a homogeneous dispersion of wavelength conversion luminescent nanoparticles is obtained by magnetic stirring and ultrasonic oscillation; (4) the prepared dispersion is spin-coated onto a clean substrate by spin coating method, and then dried on a hot plate to obtain an upconversion or downconversion luminescent film of PMMA-encapsulated luminescent nanoparticles.
[0006] The above method for preparing luminescent fluoride nanoparticles makes direct substrate film formation difficult, hence the need for the assistance of organic materials (PMMA) in film formation. However, organic materials (PMMA) are not heat-resistant, failing to achieve one of the beneficial objectives of this invention: high-temperature resistance. Furthermore, the nanoparticles prepared using this method have high defect rates, resulting in relatively weak luminescence conversion.
[0007] Currently, commonly used methods for preparing rare-earth-doped spectral conversion thin films mainly focus on physical methods such as pulsed laser deposition, magnetron sputtering deposition, and electron beam deposition. However, these methods require vacuum environments or high temperatures and necessitate the pre-fabrication of doped fluoride targets, resulting in significant waste and hindering the simple and economical preparation of wavelength conversion thin films with controllable luminescence. Other chemical preparation methods, such as spin coating, simply achieve physical adsorption between the film and the substrate, resulting in weak interfacial adhesion, which is detrimental to the practical application of the films. Furthermore, these methods cannot guarantee continuous film formation on the substrate; numerous grain boundaries or defects lead to photon scattering, resulting in low transmittance and making the films unsuitable for use in the upper light-absorbing layer of solar cells. Therefore, there is an urgent need to develop a thin film preparation method that increases transmittance, achieves efficient spectral conversion, and simultaneously ensures the film possesses the high-temperature resistance and mechanical exfoliation resistance required for practical applications. Summary of the Invention
[0008] The technical problem to be solved by the present invention is to provide a method for preparing a spectral conversion film. This method mainly addresses the dual consideration of light transmittance and light conversion function required for the spectral conversion optical film when using encapsulation materials in solar cells. When glass or quartz is used as the encapsulation material during preparation, it does not hinder the normal transmission of the solar spectrum and can increase the absorption of ultraviolet and infrared light in the solar spectrum by the battery material. On the other hand, the spectral conversion film prepared by the present invention has strong adhesion, is scratch-resistant, and is heat-resistant.
[0009] Meanwhile, the present invention provides a method for preparing a spectral conversion film, which yields a spectral conversion film with a visible light transmittance of over 90%.
[0010] Meanwhile, the present invention provides a solar cell prepared using the spectral conversion thin film of the present invention.
[0011] Meanwhile, this invention provides an application of a spectral conversion thin film in solar cells.
[0012] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a spectral conversion thin film includes the following steps: Step 1: Dissolve 0.5-5 mmol of rare earth RE water-soluble salt in a mixture of 10-100 mL ethanol and 10-100 mL oleic acid OA, stir thoroughly for 20-50 min, then add 15-150 mL triethanolamine to form a homogeneous mixed solution; add 5 mL each of 1-10 mol / L NaOH aqueous solution and 1-10 mol / L ammonium fluoride aqueous solution dropwise to the above mixed solution, and stir at 35-70℃ for at least 2 h to form a precursor solution; Step 2: Spin-coat 50-1000 μL of precursor solution onto the cleaned substrate at a speed of 1000-5000 r / min for 1-5 min. After spin-coating, dry at 80-120℃ to form a preform layer. Step 3: Dissolve 5-50 mmol of rare earth RE water-soluble salt in 10-100 mL of deionized water, add 20-200 mmol of sodium oleate (NaOA), stir thoroughly for more than 1 hour, and then sonicate at 50-100 kHz for 20-50 minutes to form a RE-OA complex solution. Add 1-20 g of polyvinylpyrrolidone (PVP) to the RE-OA complex solution and stir thoroughly for 30-60 minutes. Then add 5-20 mL of 1-10 mol / L sodium fluoride (NaF) aqueous solution and 10 mL of 1-10 mol / L sodium fluoroborate (NaBF4) aqueous solution dropwise and stir thoroughly for 30-60 minutes to form a homogeneous RE-OA complex suspension. Step 4: Insert the substrate containing the prefabricated layer vertically into the liner and fix it. The spacing between the substrates is controlled between 0.5-2 μm. Then pour in the RE-OA complex suspension prepared in Step 3. Step 5: Place the RE-OA complex suspension and the substrate containing the pre-formed layer into a reactor for hydrothermal growth at a reaction temperature of 180-220℃ and a reaction time of 18-36h. After the reaction, remove the substrate, clean and dry it to obtain a monolayer rare earth RE-doped NaYF4 large grain film continuously grown on one side of the pre-formed layer, i.e., a spectral conversion film.
[0013] The substrate is glass or quartz, which is 300mm long and wide and 3mm thick.
[0014] The inner liner is made of polytetrafluoroethylene; the volume of the inner liner is 100 mL; the reactor is made of stainless steel.
[0015] The stirring rate is 100-1000 r / min; the dropping rate is 30-100 μL / min.
[0016] In step five, the cleaning process involves ultrasonically cleaning with alcohol and deionized water several times.
[0017] In step five, drying is achieved by blowing with high-purity nitrogen gas.
[0018] Rare earth RE water-soluble salts include yttrium (Y), and also one or more of erbium, terbium, ytterbium, holmium, praseodymium, europium, samarium, and strontium; rare earth RE water-soluble salts include rare earth RE chlorides, rare earth RE nitrates, or rare earth RE acetates.
[0019] The spectral conversion thin film obtained by the preparation method of the present invention has a grain size of 2-5 μm in the rare earth RE-doped NaYF4 large grain film; the visible light transmittance is above 90%.
[0020] Solar cells prepared using the spectral conversion thin film of the present invention.
[0021] The application of the spectral conversion thin film of the present invention in solar cells.
[0022] The present invention has the following beneficial effects: The present invention provides a fluoride film with spectral conversion capability that can be deposited on glass or quartz, exhibiting strong adhesion and high transmittance.
[0023] This invention achieves up / down spectral conversion capabilities in different bands by changing the doping of different rare earth elements, and can also achieve simultaneous up and down spectral conversion.
[0024] This invention achieves the chemical preparation of a single-layer, continuous large-grained fluoride film with a particle size of 2 μm or more by adding PVP, sodium fluoroborate, and adjusting the substrate placement distance.
[0025] This invention is simple and controllable, and can be mass-produced using existing production line equipment. The type, content, and thickness of the doped elements in the thin film are controllable, making it relatively easy to adjust the spectral conversion efficiency and form, resulting in high transmittance. The thin film exhibits strong adhesion to the substrate (it does not detach under ultrasonic vibration), and a wide range of substrate materials can be selected, such as ultra-white float glass, ordinary soda-lime glass, and quartz glass. It can even be fabricated directly on the device surface, for example, directly grown on the silicon wafer surface (fluorides are chemically stable and do not react with silicon, perovskite, or other materials).
[0026] This invention improves the utilization rate of the solar spectrum in solar cells. Infrared rays that cannot be absorbed and ultraviolet rays with excessive energy can be converted into photons with high utilization rates through this spectral conversion film. Furthermore, this film does not block or absorb visible-near-infrared photons, meaning it does not reduce transmittance. This invention is of great significance for improving the conversion efficiency of solar cells. Attached Figure Description
[0027] Figure 1 This is a flowchart of the present invention; Figure 2 This is a scanning electron microscope image of the spectral conversion thin film. Figure 3 A comparison diagram of the up / down spectral conversion functions of spectral conversion thin films; Figure 4 Thermogravimetric analysis curve of the spectral conversion thin film of the present invention; Figure 5 This is a graph showing the adhesion of a spectral conversion thin film. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. The specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0029] Example 1 A method for preparing a spectral conversion thin film, characterized by comprising the following steps: Step 1: Dissolve 2 mmol of rare earth RE water-soluble salt in a mixture of 10 mL ethanol and 10 mL oleic acid OA. Set the stirring speed to 500 r / min and the stirring time to 30 min. After thorough stirring, add 15 mL of triethanolamine to form a homogeneous mixed solution. Add 5 mL each of 2 mol / L NaOH aqueous solution and 5 mol / L ammonium fluoride aqueous solution dropwise to the above mixed solution at 50 μL / min. Stir at 500 r / min for 2 h at 50 °C to form a precursor solution. Step 2: Spin-coat 500 μL of precursor solution onto the cleaned substrate at a spin speed of 3000 r / min for 3 min. After spin coating, dry at 100°C to form a preform layer. Step 3: Dissolve 10 mmol of rare earth RE water-soluble salt in 50 mL of deionized water, add 20 mmol of sodium oleate (NaOA), stir at 200 r / min for 1 h, and then sonicate at 50 kHz for 30 min to form RE-OA complex solution. Add 5 g of polyvinylpyrrolidone (PVP) to the RE-OA complex solution and stir at 500 r / min for 40 min. Then add 10 mL of 5 mol / L sodium fluoride (NaF) aqueous solution and 10 mL of 5 mol / L sodium fluoroborate (NaBF4) aqueous solution at a rate of 50 μL / min and stir at 500 r / min for 45 min to form a homogeneous RE-OA complex suspension. Step 4: Insert the matrix containing the pre-prepared layer vertically into the 100mL liner and fix it, with the matrix spacing controlled at 1μm. Then pour in the RE-OA complex suspension prepared in Step 3. Step 5: The RE-OA complex suspension and the substrate containing the pre-formed layer are placed in a reactor for hydrothermal growth at a reaction temperature of 200°C and a reaction time of 24 hours. After the reaction, the substrate is removed, cleaned, and dried to obtain a monolayer rare earth RE-doped NaYF4 large grain film continuously grown on one side of the pre-formed layer, which is a spectral conversion film.
[0030] The substrate is glass or quartz, which is 300mm long and wide and 3mm thick.
[0031] The inner lining is made of polytetrafluoroethylene.
[0032] The reactor is made of stainless steel.
[0033] In step five, the cleaning process involves ultrasonically cleaning with alcohol and deionized water several times.
[0034] In step five, drying is achieved by blowing with high-purity nitrogen gas.
[0035] Figure 3 (a) is a thin film prepared with yttrium and erbium as RE elements, that is, the rare earth RE in the rare earth RE water-soluble salt is yttrium Y and erbium. The visible light transmittance of this film is 93.5%.
[0036] Figure 3 (b) The RE elements in the prepared film are yttrium, terbium and ytterbium, that is, the rare earth REs in the rare earth RE water-soluble salt are yttrium Y, terbium and ytterbium. The visible light transmittance of the film is 93.2%.
[0037] The water-soluble salts of rare earth elements (RE) are rare earth chlorides.
[0038] The spectral conversion film obtained by the preparation method in this embodiment has a grain size of 2-5 μm in the rare earth RE-doped NaYF4 large grain film; the visible light transmittance is above 93%.
[0039] A solar cell prepared using the spectral conversion thin film of this embodiment.
[0040] The application of the spectral conversion thin film in solar cells in this embodiment.
[0041] The dried substrate was tested using a scanning electron microscope and found that ( Figure 2 The side with the pre-formed layer has a continuous film, while the product attached to the side without the pre-formed layer can be easily removed during ultrasonic oscillation cleaning. This is because the addition of the pre-formed layer causes sodium yttrium fluoride (NaYF4) crystal nuclei to be pre-formed on one side of the substrate. During hydrothermal growth, the crystal nuclei absorb RE-OA complexes and grow continuously, forming a good chemical-physical mixed bond with the substrate.
[0042] Figure 2 (a) is a hydrothermal grown film without the addition of PVP and NaBF4 (the only difference from this embodiment is that PVP and NaBF4 are not added), with more grain boundaries and a multilayer film, and a low visible light transmittance of 85%. Figure 2 (b) The film is grown hydrothermally with appropriate amounts of PVP and NaBF4. The film is grown with large grains, with grain size reaching 2-5 μm. There are very few grain boundaries and defects, which is conducive to photon transmission. The visible light transmittance test is over 90%, which meets the transmittance requirements of encapsulation glass for solar cells.
[0043] Furthermore, if the substrate spacing is too large (greater than 5 μm), the film will be too thick, thus reducing transmittance. This is because when the substrate spacing is within a suitable range (0.5-2 μm), the RE-OA complex in the solution enters the tiny space under the drive of capillary force, and a small amount of complex can fill the pores and grow with the crystal clusters in the preform. Under the dual action of surfactant (PVP) and oxidation inhibitor (NaBF4), when it grows to a monolayer, it cannot continue to grow because there is no RE-OA complex in the space, thus achieving excellent transmittance.
[0044] Changing the type of rare earth elements (such as erbium, terbium, ytterbium, holmium, praseodymium, europium, samarium, strontium, etc.) or using multiple types of doping can achieve excellent up / down spectral conversion capabilities or simultaneously achieve both up and down spectral conversion capabilities. For example... Figure 3 As shown, Figure 3(a) Thin films prepared with yttrium and erbium as RE elements (and thin films prepared without PVP and NaBF4) exhibited a strong spectral upconversion effect under 980nm laser irradiation. Both types of films converted 980nm infrared light into 525-575nm green light and 625-700nm red light. Photons in both regions can be absorbed by solar cells and converted into electrons, enabling solar cells to utilize a wider range of the solar spectrum. Because the thin films grown with PVP and NaBF4 have larger grain sizes and fewer defects, the probability of photon scattering and recombination is reduced, resulting in higher upconversion luminescence intensity. This indicates that adding these two substances greatly improves the growth and luminescence efficiency of the thin films. Figure 3 (b) The RE elements in the prepared thin film are yttrium, terbium, and ytterbium (as well as the thin film prepared without the addition of PVP and NaBF4). After irradiation with a 375nm laser, emission peaks of 450-650nm and 950-1100nm were successfully observed, which correspond to the characteristic emission peaks of terbium and ytterbium, respectively. This indicates that the thin film prepared by this technical solution can successfully achieve downconversion luminescence, which can convert high-energy ultraviolet photons (solar cells cannot convert all the energy of high-energy ultraviolet light into electrical energy, but will lose the unconverted energy as heat energy) into visible light and near-infrared photons with higher absorption rates. Similarly, the quality of the thin film affects the luminescence intensity. The higher the quality of the thin film, the better the luminescence intensity and the higher its conversion efficiency.
[0045] Figure 4 The thermogravimetric analysis curve of the thin film shows that within the temperature range that the glass can withstand (below 600℃), the weight of the film is not lost (the slight decrease is due to the volatilization of residual organic matter in the film prepared by the hydrothermal method), and the film does not undergo any morphological changes (softening, flow, etc.) after heating, indicating that the film has the heat resistance temperature of fluoride (greater than 1000℃), which is an effect that cannot be achieved by adding organic matter to prepare the film.
[0046] The prepared films underwent subsequent cleaning with ultrasonic vibration for over 30 minutes. Films grown using the pre-layer hydrothermal method were not damaged by ultrasonic cleaning, demonstrating that films grown by this method have stronger adhesion than most chemically grown films. To further verify the beneficial effects of adding PVP and NaBF4, a tape peel test was used. Figure 2 The test results for the two types of film adhesion are as follows: Figure 5 . Figure 5 The film on the left, without the addition of PVP and NaBF4, showed obvious signs of peeling after being taped five times. In contrast, the film on the right (grown with the addition of PVP and NaBF4) did not show obvious signs of peeling after being taped five times, indicating that the film has a high degree of adhesion to the substrate.
[0047] Example 2
[0048] A method for preparing a spectral conversion thin film includes the following steps: Step 1: Dissolve 0.5 mmol of rare earth RE nitrate in a mixture of 100 mL ethanol and 100 mL oleic acid OA. Set the stirring speed to 100 r / min and the stirring time to 20 min. After thorough stirring, add 150 mL of triethanolamine to form a homogeneous mixed solution. Add 5 mL each of 1 mol / L NaOH aqueous solution and 1 mol / L ammonium fluoride aqueous solution dropwise to the above mixed solution at a rate of 30 μL / min. Stir at 100 r / min for 3 h at 35 °C to form a precursor solution. Step 2: Spin-coat 1000 μL of precursor solution onto a clean glass or quartz substrate with dimensions of 300 mm in length and width and a thickness of 3 mm. Set the spin speed to 1000 r / min and the spin coating time to 1 min. After spin coating, dry at 80°C to form a preform layer. Step 3: Dissolve 5 mmol of rare earth RE nitrate in 10 mL of deionized water, add 200 mmol of sodium oleate (NaOA), stir at 100 r / min for 1.5 h, then sonicate at 100 kHz for 20 min to form a RE-OA complex solution. Add 1 g of polyvinylpyrrolidone (PVP) to the RE-OA complex solution and stir at 100 r / min for 30 min. Then add 5 mL of 1 mol / L sodium fluoride (NaF) aqueous solution and 10 mL of 1 mol / L sodium fluoroborate (NaBF4) aqueous solution at a rate of 30 μL / min and stir at 100 r / min for 30 min to form a homogeneous RE-OA complex suspension. Step 4: Insert the substrate containing the pre-formed layer vertically into a 100 mL polytetrafluoroethylene liner and fix it in place. The substrate spacing is controlled at 0.5 μm. Then pour in the RE-OA complex suspension prepared in Step 3. Step 5: The polytetrafluoroethylene liner containing the RE-OA complex suspension and the substrate containing the pre-formed layer is placed in a stainless steel reactor for hydrothermal growth at a reaction temperature of 180°C and a reaction time of 18 hours. After the reaction, the substrate is removed, ultrasonically cleaned several times with alcohol and deionized water, and then dried with high-purity nitrogen to obtain a single-layer rare earth RE-doped NaYF4 large-grain film continuously grown on one side of the pre-formed layer, i.e., a spectral conversion film.
[0049] In this embodiment, the RE elements are yttrium and holmium.
[0050] The spectral conversion film obtained by the preparation method in this embodiment has a grain size of 2-5 μm in the rare earth RE-doped NaYF4 large grain film; the visible light transmittance is 93%.
[0051] A solar cell prepared using the spectral conversion thin film of this embodiment.
[0052] The application of the spectral conversion thin film in solar cells in this embodiment.
[0053] Example 3
[0054] A method for preparing a spectral conversion thin film includes the following steps: Step 1: Dissolve 5 mmol of rare earth RE acetate in a mixture of 50 mL of ethanol and 50 mL of oleic acid OA. Set the stirring speed to 1000 r / min and the stirring time to 50 min. After thorough stirring, add 100 mL of triethanolamine to form a homogeneous mixed solution. Add 5 mL each of 10 mol / L NaOH aqueous solution and 10 mol / L ammonium fluoride aqueous solution dropwise to the above mixed solution at a rate of 100 μL / min. Stir at 1000 r / min for 2.5 h at 70 °C to form a precursor solution. Step 2: Spin-coat 50 μL of precursor solution onto a clean glass or quartz substrate with dimensions of 300 mm in length and width and a thickness of 3 mm. Set the spin speed to 5000 r / min and the spin coating time to 5 min. After spin coating, dry at 120℃ to form a preform layer. Step 3: Dissolve 50 mmol of rare earth RE acetate in 100 mL of deionized water, add 100 mmol of sodium oleate (NaOA), stir at 1000 r / min for 2 h, then sonicate at 80 kHz for 50 min to form a RE-OA complex solution. Add 20 g of polyvinylpyrrolidone (PVP) to the RE-OA complex solution and stir at 1000 r / min for 60 min. Then add 20 mL of 10 mol / L sodium fluoride (NaF) aqueous solution and 10 mL of 10 mol / L sodium fluoroborate (NaBF4) aqueous solution at a rate of 100 μL / min and stir at 1000 r / min for 60 min to form a homogeneous RE-OA complex suspension. Step 4: Insert the substrate containing the pre-formed layer vertically into a 100 mL polytetrafluoroethylene liner and fix it in place. The spacing between the substrates is controlled at 2 μm. Then pour in the RE-OA complex suspension prepared in Step 3. Step 5: The polytetrafluoroethylene liner containing the RE-OA complex suspension and the substrate containing the pre-formed layer is placed in a stainless steel reactor for hydrothermal growth at a reaction temperature of 220°C and a reaction time of 36 hours. After the reaction, the substrate is removed, ultrasonically cleaned several times with alcohol and deionized water, and then dried with high-purity nitrogen to obtain a single-layer rare earth RE-doped NaYF4 large-grain film continuously grown on one side of the pre-formed layer, i.e., a spectral conversion film.
[0055] In this embodiment, the RE element is yttrium, praseodymium, and europium.
[0056] The spectral conversion film obtained by the preparation method in this embodiment has a grain size of 2-5 μm in the rare earth RE-doped NaYF4 large grain film; the visible light transmittance is 92%.
[0057] A solar cell prepared using the spectral conversion thin film of this embodiment.
[0058] The application of the spectral conversion thin film in solar cells in this embodiment.
[0059] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a spectral conversion thin film, characterized in that: Includes the following steps: Step 1: Dissolve 0.5-5 mmol of rare earth RE water-soluble salt in a mixture of 10-100 mL ethanol and 10-100 mL oleic acid OA, stir thoroughly for 20-50 min, then add 15-150 mL triethanolamine to form a homogeneous mixed solution; add 5 mL each of 1-10 mol / L NaOH aqueous solution and 1-10 mol / L ammonium fluoride aqueous solution dropwise to the above mixed solution, and stir at 35-70℃ for at least 2 h to form a precursor solution; Step 2: Spin-coat 50-1000 μL of precursor solution onto the cleaned substrate at a speed of 1000-5000 r / min for 1-5 min. After spin-coating, dry at 80-120℃ to form a preform layer. Step 3: Dissolve 5-50 mmol of rare earth RE water-soluble salt in 10-100 mL of deionized water, add 20-200 mmol of sodium oleate (NaOA), stir thoroughly for more than 1 hour, and then sonicate at 50-100 kHz for 20-50 minutes to form a RE-OA complex solution. Add 1-20 g of polyvinylpyrrolidone (PVP) to the RE-OA complex solution and stir thoroughly for 30-60 minutes. Then add 5-20 mL of 1-10 mol / L sodium fluoride (NaF) aqueous solution and 10 mL of 1-10 mol / L sodium fluoroborate (NaBF4) aqueous solution and stir thoroughly for 30-60 minutes to form a homogeneous RE-OA complex suspension. Step 4: Insert the substrate containing the prefabricated layer vertically into the liner and fix it. The spacing between the substrates is controlled between 0.5-2 μm. Then pour in the RE-OA complex suspension prepared in Step 3. Step 5: Place the RE-OA complex suspension and the substrate containing the pre-formed layer into a reactor for hydrothermal growth at a reaction temperature of 180-220℃ and a reaction time of 18-36h. After the reaction, remove the substrate, clean and dry it to obtain a monolayer rare earth RE-doped NaYF4 large grain film continuously grown on one side of the pre-formed layer, i.e., a spectral conversion film.
2. The preparation method according to claim 1, characterized in that: The substrate is glass or quartz, which is 300mm long and wide and 3mm thick.
3. The preparation method according to claim 1, characterized in that: The inner liner is made of polytetrafluoroethylene; the volume of the inner liner is 100 mL; the reactor is made of stainless steel.
4. The preparation method according to claim 1, characterized in that: The stirring rate is 100-1000 r / min; the dropping rate is 30-100 μL / min.
5. The preparation method according to claim 1, characterized in that: In step five, the cleaning process involves ultrasonically cleaning with alcohol and deionized water several times.
6. The preparation method according to claim 1, characterized in that: In step five, drying is achieved by blowing with high-purity nitrogen gas.
7. The preparation method according to claim 1, characterized in that: Rare earth RE water-soluble salts include yttrium (Y), and also one or more of erbium, terbium, ytterbium, holmium, praseodymium, europium, samarium, and strontium; rare earth RE water-soluble salts include rare earth RE chlorides, rare earth RE nitrates, or rare earth RE acetates.
8. The spectral conversion thin film obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The grain size in rare earth RE-doped NaYF4 large-grain thin films is 2-5 μm; the visible light transmittance is over 90%.
9. A solar cell prepared using the spectral conversion thin film as described in claim 8.
10. The application of the spectral conversion thin film according to claim 8 in solar cells.
Citation Information
Patent Citations
A method for preparing a wavelength-converting light-emitting thin film
CN109929203B
Under-light conversion layer for silicon solar cell and manufacturing method of under-light conversion layer
CN105870239A
Preparation method of spectrum conversion nanorod array
CN114163138A
